Microwave dielectric study of Pearl Millet (Pennisetum typhoides) at 9.85 GHz frequency - Karhale, G A; Fugare, M K; Kalamse, G M (International Multidisciplinary Research Journal, 2012)
Values of dielectric constant ( ), dielectric loss ( ), relaxation time (ðœp), conductivity (σp) and moisture content of pulverized Pearl millet were measured for different packing densities at 9.85 GHz microwave frequency and at different temperature ( 20ËšC, 35ËšC and 50ËšC). Experimental results on powders of different packing fractions (δr) were used to obtain transformation to 100% solid bulk using correlation formulae of Landau-Lifshitz-Looyenga and Bottcher. Moisture content was measured by Thermo- gravimetric method. It is found that, there was fair agreement between the calculated values of dielectric parameters and the values obtained experimentally for solid bulk. This shows cohesion in the particles of Cinnamon bark powders under investigation.